2022
DOI: 10.1021/acsomega.2c06075
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Doping to Control the Band Gap of Ascorbic Acid: A Theoretical Study

Abstract: Ascorbic acid is an important antioxidant agent that acts as an electron donor and is involved in many physiological processes. Structural modification in ascorbic acid is a subject of extensive biochemical research due to its involvement in a variety of relevant phenomena including electron transport, complex redox reactions, neurochemical reactions, enzymatic reactions, and chemotherapeutic potential. In this work, the structure of ascorbic acid is modified via doping with the first three members of the halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The peaks at 1762 and 1683 cm –1 are attributed to the CO and CC stretching vibrations, respectively. These absorption peaks mentioned above are characteristic peaks of AA. , The peaks at 1565 and 1481 cm –1 are attributed to the CC stretching vibration of the quinoid ring and benzene ring, which are from the PANI film.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks at 1762 and 1683 cm –1 are attributed to the CO and CC stretching vibrations, respectively. These absorption peaks mentioned above are characteristic peaks of AA. , The peaks at 1565 and 1481 cm –1 are attributed to the CC stretching vibration of the quinoid ring and benzene ring, which are from the PANI film.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These absorption peaks mentioned above are characteristic peaks of AA. 46,47 The peaks at 1565 and 1481 cm −1 are attributed to the C�C stretching vibration of the quinoid ring and benzene ring, which are from the PANI film.…”
Section: Catalytic Mechanism Of Pani-pa/spce To Ascorbic Acidmentioning
confidence: 99%
“…Also, we investigated the behavior of doping of ascorbic acid with halogens and the effect of changes in the band gap when doping took place and concluded that the band gap of ascorbic acid responded to the introduction of halogen atoms based on their position in the electronegative series, thus increasing the effectiveness of ascorbic acid in radical scavenging in the human body. 46 In this work, the dopamine molecule was doped with the first three members of the halogen family (fluorine, chlorine, and bromine) to analyze their effects on some spectroscopic and electronic properties, such as NMR, Fourier transform infrared (FT-IR) spectroscopy, band gap energy, potential energy map, and density of states (DOS). The obtained theoretical results were compared with those in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As the band gap is the threshold for photons to be absorbed, determination of the variation of the band gap will give us a measure of effectiveness of dopamine for curing. Research in band gap control can provide a complete control in the activity of the title molecule in the reaction mechanism of the molecule in the human body. Free radicals and harmful chemical species in the human body always originate from aerobic metabolism and other processes, like smoking, use of pesticides, herbicides, and drugs, and ionization radiation. , All these process can change the balance of the oxidation–reduction reaction in the body, which leads to problems like hypertension, cancer, cardiovascular diseases, and neurodegenerative disorders such as PD and Huntington’s disease. That is why this research focuses on improving the efficiency of dopamine activity to produce molecules that will balance oxidants and anti-oxidants present in the body, which will be helpful for curing many detected and undetected diseases. Also, we investigated the behavior of doping of ascorbic acid with halogens and the effect of changes in the band gap when doping took place and concluded that the band gap of ascorbic acid responded to the introduction of halogen atoms based on their position in the electronegative series, thus increasing the effectiveness of ascorbic acid in radical scavenging in the human body …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation